THE QUALITY OF PUBLIC SERVICE DELIVERY AT MIMOZA MULTIMEDIA GORONTALO - Rahim, Rendy Rianto; Husain, Walidun; Tui, Fenti Prihatini Dance (Public Policy Journal, 2020)
The research aims to analyze and describe (1) the quality of service delivery in terms of customers’ satisfaction at Mimoza Multimedia and (2) the factors affecting the quality of service delivery at Mimoza Multimedia. The research method used is qualitative method. The data are the primary data collected through interviews. The data analysis used is Miles and Huberman’s analysis model. The research findings indicate that (1) Mimoza Multimedia Gorontalo has been able to provide public services for society. However, service delivery should be improved through more progressive service polices and evaluations to elevate customers’ satisfaction level. Some aspects of public service delivery that fulfill customers’ satisfaction are adequate facilities and infrastructures, guarantee or compensation to unsatisfactory services, and empathy shown by employees. Meanwhile, responsiveness and reliability are two aspects which need improvement through capacity building in terms of the public service delivery at Mimoza Multimedia Gorontalo and (2) The service delivery at Mimoza Multimedia Gorontalo relies on the quality of human resources, communication between the employees, and communication between the employees and customers. Customers’ satisfaction depends on competent and committed human resources to delivering public services in accordance with service principles. Moreover, the supporting factor is communication. Services without good communication will not satisfy customers.